Flexoelectricity-induced retention failure in ferroelectric films. (1st September 2020) - Zou, M.J.; Tang, Y.L.; Zhu, Y.L.; Wang, Y.J.; Feng, Y.P.; Han, M.J.; Zhang, N.B.; Ma, J.Y.; Geng, W.R.; Hu, W.T.; Guo, X.W.; Wu, B.; et al.
Abstract: Retention failure is deleterious on ferroelectric domain stability, resulting in data loss in ferroelectric memories. However, the understanding of the origin of retention failure remains a challenge for the lack of a direct experimental evidence. Here, using a combination of piezoelectric force microscopy, atomic-scale scanning transmission electron microscopy and reciprocal space mapping, we report that the polarization retention failure is caused by a strain gradient induced flexoelectric field in tetragonal ferroelectric films. Atomic imaging reveals that the strain gradient is introduced by tensile strains, which is resultant from the vertically distributed Pb-rich anti-phase domains. This strain gradient couples with polarizations and results in flexoelectric fields in the films, leading to the retention failure in the films. Our study directly underlines the atomic mechanisms behind the strain gradient induced macroscopic retention failure behavior and clarifies the effect of local strain state on domain relaxation processes, thus can shed light on further understanding and improving the retention properties of oxide ferroelectrics. Graphical abstract: Image, graphical abstract